2021
DOI: 10.1186/s12967-021-03010-1
|View full text |Cite
|
Sign up to set email alerts
|

Chronotype: what role in the context of gastroenteropancreatic neuroendocrine tumors?

Abstract: Background Chronotype is defined as a trait determining the subject circadian preference in behavioral and biological rhythms relative to external light–dark cycle. Although individual differences in chronotype have been associated with an increased risk of developing some types of cancer, no studies have been carried out in gastroenteropancreatic neuroendocrine tumors (GEP-NET). Materials We investigate the differences in chronotype between 109 GE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 61 publications
1
17
0
2
Order By: Relevance
“…However, little data were available on association between chronotype and digestive tract cancer. A case‐control study including a total of 318 participants found that patients with gastroenteropancreatic neuroendocrine tumors had a higher percentage of having evening chronotype compared to the healthy controls 9 . That study further showed that a higher chronotype score indicating a higher adherence to morningness was also associated with lower risk of metastasis, grading G2 and progressive disease 9 .…”
Section: Discussionmentioning
confidence: 92%
“…However, little data were available on association between chronotype and digestive tract cancer. A case‐control study including a total of 318 participants found that patients with gastroenteropancreatic neuroendocrine tumors had a higher percentage of having evening chronotype compared to the healthy controls 9 . That study further showed that a higher chronotype score indicating a higher adherence to morningness was also associated with lower risk of metastasis, grading G2 and progressive disease 9 .…”
Section: Discussionmentioning
confidence: 92%
“…The available data also suggested that diabetes conferred an increased risk for pancreatic NEN (OR = 2.76; 95% CI: 1.65–4.64; I2 = 55.3; p = 0.090), the risk being even higher for recent onset diabetes (OR = 12.80; 95% CI: 2.47–66.42; I2 = 55.3; p = 0.135). A recent Italian case-control study, that evaluated the influence of chronotype on WD GEP-NEN, concluded that a higher proportion of evening chronotype and unhealthy metabolic profile, along with smoking and sedentary habits, was observed in patients with GEP-NEN when compared to healthy controls [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were published by our group [ 17 ]. Evening chronotype also seems to influence GEP-NEN prognosis, as it showed to be associated with distant metastasis, a higher grade, and progressive disease [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lifestyle habits were determined in all study participants through a standard questionnaire [27][28][29][30].…”
Section: Methodsmentioning
confidence: 99%